Delivery of infection from asymptomatic carriers of COVID-19 in a familial cluster - Ye, Feng; Xu, Shicai; Rong, Zhihua; Xu, Ronghua; Liu, Xiaowei; Deng, Pingfu; Liu, Hai; Xu, Xuejun (International journal of infectious diseases, 2020)
•There are more than 100,000 confirmed COVID-19 cases, with spread to over 100 countries as of 2020-03-08.•Asymptomatic carriers during the incubation period can be a potential infection source of COVID-19.•Person-to-person transmission has been documented; asymptomatic carriers should be a focus for disease prevention. With the ongoing outbreak of COVID-19 around the world, it has become a worldwide health concern. One previous study reported a family cluster with an asymptomatic transmission of COVID-19. Here, we report another series of cases and further demonstrate the repeatability of the transmission of COVID-19 by pre-symptomatic carriers. A familial cluster of five patients associated with COVID-19 was enrolled in the hospital. We collected epidemiological and clinical characteristics, laboratory outcomes from electronic medical records, and also verified them with the patients and their families. Among them, three family members (Case 3/4/5) had returned from Wuhan. Additionally, two family members, those who had not traveled to Wuhan, also contracted COVID-19 after contacting with the other three family members. Case 1 developed severe pneumonia and was admitted to the ICU. Case 3 and Case 5 presented fever and cough on days two through three of hospitalization and had ground-glass opacity changes in their lungs. Case 4 presented with diarrhea and pharyngalgia after admission without radiographic abnormalities. Case 2 presented no clinical nor radiographic abnormalities. All five cases had an increasing level of C-reactive protein. Our findings indicate that COVID-19 can be transmitted by asymptomatic carriers during the incubation period.